The studios after the studios : neoclassical Hollywood (1970-2010) - Connor, J. D. (Post 45., 2015)
Modern Hollywood is dominated by a handful of studios: Columbia, Disney, Fox, Paramount, Universal, and Warner Bros. Threatened by independents in the 1970s, they returned to power in the 1980s, ruled unquestioned in the 1990s, and in the new millennium are again beseiged. But in the heyday of this new classical era, the major studios movies - their stories and styles - were astonishingly precise biographies of the studios that made them. Movies became product placements for their studios, advertising them to the industry, to their employees, and to the public at large. If we want to know how.